pyfds 0.3.1 - modular field simulation tool - Claes, Leander; Webersen, Manuel

Zwischen Beutesuche und politischen Ambitionen. Die Normannen an Rhein und Maas zwischen 880 und 892 - Kamp, Hermann (Zeitschrift des Aachener Geschichtsvereins)

‚Schelmische‘ Post-DDR-Romane: Ingo Schulzes „Peter Holtz“ und Lea Streisands „Hufeland, Ecke Bötzow“ - Elit, Stefan (‚Topographisches‘ Schreiben: Lea Streisand, Paderborn, Wintersemester 2022/2023)

Characterizing Microheterogeneity in Liquid Mixtures via Local Density Fluctuations - Lass, Michael; Kenter, Tobias; Plessl, Christian; Brehm, Martin (Entropy)
We present a novel approach to characterize and quantify microheterogeneity and microphase separation in computer simulations of complex liquid mixtures. Our post-processing method is based on local density fluctuations of the different constituents in sampling spheres of varying size. It can be easily applied to both molecular dynamics (MD) and Monte Carlo (MC) simulations, including periodic boundary conditions. Multidimensional correlation of the density distributions yields a clear picture of the domain formation due to the subtle balance of different interactions. We apply our approach to the example of force field molecular dynamics simulations of imidazolium-based ionic liquids with different side chain lengths at different temperatures, namely 1-ethyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride, which are known to form distinct liquid domains. We put the results into the context of existing microheterogeneity analyses and demonstrate the advantages and sensitivity of our novel method. Furthermore, we show how to estimate the configuration entropy from our analysis, and we investigate voids in the system. The analysis has been implemented into our program package TRAVIS and is thus available as free software.

'Topographisches‘ Schreiben: Lea Streisand. Paderborn Wintersemester 2022/23

Klopstocks lyrisches Spätwerk. Perspektivwechsel und Blickerweiterungen - Elit, Stefan („Wer wird nicht einen Klopstock loben?“ Friedrich Gottlieb Klopstocks poetische Innovationen und ihre produktive Rezeption)

‚Topographisches‘ Schreiben. Lea Streisand, Paderborn Wintersemester 2022/23: Die 41. Gastdozentur für Schriftstellerinnen und Schriftsteller. Zur Einführung. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Sich selbst erzählen. Lea Streisands autofiktionales Erzählen. - Eke, Norbert (‚Topographisches‘ Schreiben: Lea Streisand – Paderborn Wintersemester 2022/23)

Digitale Plattformen im industriellen Mittelstand

Digitale Plattformen im industriellen Mittelstand

Belgischer Symbolismus zum Be/Greifen nah. Museumskoffer zum Werk von Léon Spilliaert und George Minne.
Der belgische Symbolismus wurde in den letzten Jahrzehnten neu entdeckt. Während Künstler wie Léon Spilliaert und George Minne lange ein Geheimtipp waren, ziehen sie nun ein großes Publikum in ihren Bann. Dennoch gelten viele Werke dieser Kunstströmung bis heute aufgrund der sie prägenden anspruchsvollen Formensprache, verborgenen Bedeutungen und mystischen Visionen als ebenso anziehend wie unergründlich. Die hier vorgestellten siebzehn Museumskoffer bieten vielfältige Zugänge, sie in ihrem kulturellen und kunsthistorischen Kontext zu entdecken und zu verstehen: Sie machen kulturelles Lernen zu einem ganzheitlichen Erlebnis und öffnen Türen zu neuen Welten. Ergänzend stellt der Katalog Texte zum Medium ‚Museumskoffer‘, zum belgischen Symbolismus und weiteres relevantes Informationsmaterial zur Verfügung.
Keywords: Belgischer Symbolismus; Museumskoffer; León Spilliaert; George Minne

31 Sprachbildung im berufsbezogenen Mathematikunterricht. - Prediger, Susanne; Wessel, Lena (Berufs-und Fachsprache Deutsch in Wissenschaft und Praxis)

Implementation of Different Communication Structures for a Rocket Chip Based RISC-V Grid of Processing Cells - Luchterhandt, Lars; Nellius, Tom; Beck, Robert; Dömer, Rainer; Kneuper, Pascal; Müller, Wolfgang; Sadiye, Babak (MBMV 2024 - 27. Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen“)
RISC-V has received worldwide acceptance in the industry and by the academic community. As of today, multiple RISC-V applications and variants are under investigation for embedded IoT systems, from resource-limited single-core processors up to multi-core systems for High-Performance Computing (HPC). Recently, the Grid of Processing Cells (GPC) platform has been proposed as a scalable parallel grid-oriented network of processor cores with local memories. This paper describes a prototype design of the GPC platform for hardware implementation at Register-Transfer Level (RTL) based on modified RISC-V Rocket processors with scratchpad memories. It introduces a scalable Chisel-based implementation of the modified Rocket cores with RTL generation and a functional test using Verilator simulation. This work also includes the adaptation of the Chipyard software toolchain to extend the compiler to multi-core grids with different local address spaces.

A Scalable RISC-V Hardware Platform for Intelligent Sensor Processing - Palomero Bernardo, Paul; Schmid, Patrick; Bringmann, Oliver; Iftekhar, Mohammed; Sadiye, Babak; Müller, Wolfgang; Koch, Andreas; Jentsch, Eyck; Sauer, Axel; Feldner, Ingo; Ecker, Wolfgang (DATE 24 - Design Automation and Test in Europe)

„Wir wollen mitreden!“ – Entwicklung und Validierung von Skalen zur Erfassung motivationaler Regulation bei der Teilnahme an Befragungen zur Evaluation des Studiums (SMR-Eval) - Koppenborg, Markus; Klingsieck, Katrin B. (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung: Für die Evaluation und Qualitätsentwicklung von Studium und Lehre werden häufig quantitative Befragungen von Studenten eingesetzt. Jedoch ist häufig unklar, aus welcher Motivation Studenten an den Befragungen teilnehmen und inwieweit unterschiedliche motivationale Regulationsstile mit dem Antwortverhalten im Fragebogen zusammenhängen. Ausgehend von der Selbstbestimmungstheorie der Motivation nach Deci und Ryan stellt der Beitrag die Entwicklung der Skalen zur motivationalen Regulation bei Befragungen zur Evaluation (SMR-Eval) vor. Studie 1 zeigt die fünffaktorielle Struktur des Instruments. Studie 2 weist auf eine starke Messinvarianz bezüglich Geschlecht, Abschlussziel und Fakultät hin. Korrelationen mit Drittvariablen belegen die konvergente Validität der fünf Subskalen. In Studie 3 werden latente Profilanalysen über die fünf Regulationsstile berechnet. Die Ergebnisse zeigen vier Profile, welche sich inhaltlich plausibel im Antwortverhalten der Befragten unterscheiden und damit Hinweise auf die Kriteriumsvalidität der Skalen geben. Diskutiert werden theoretische und praktische Implikationen für Evaluationsvorhaben an Hochschulen sowie Übertragungsmöglichkeiten auf andere Evaluationsgegenstände.
Keywords: Developmental and Educational Psychology

Cold denaturation of DNA origami nanostructures - Dornbusch, Daniel; Hanke, Marcel; Tomm, Emilia; Kielar, Charlotte; Grundmeier, Guido; Keller, Adrian; Fahmy, Karim (Chemical Communications)
The coupling of structural transitions to heat capacity changes leads to destabilization of macromolecules at both, elevated and lowered temperatures. DNA origami not only exhibit this property but also provide...
Keywords: Materials Chemistry; Metals and Alloys; Surfaces; Coatings and Films; General Chemistry; Ceramics and Composites; Electronic; Optical and Magnetic Materials; Catalysis

Playing games with QCA: Measuring the explanatory power of single conditions with the Banzhaf index - Haake, Claus-Jochen; Schneider, Martin (Journal of International Management)
Qualitative comparative analysis (QCA) enables researchers in international management to better understand how the impact of a single explanatory factor depends on the context of other factors. But the analytical toolbox of QCA does not include a parameter for the explanatory power of a single explanatory factor or “condition”. In this paper, we therefore reinterpret the Banzhaf power index, originally developed in cooperative game theory, to establish a goodness-of-fit parameter in QCA. The relative Banzhaf index we suggest measures the explanatory power of one condition averaged across all sufficient combinations of conditions. The paper argues that the index is especially informative in three situations that are all salient in international management and call for a context-sensitive analysis of single conditions, namely substantial limited diversity in the data, the emergence of strong INUS conditions in the analysis, and theorizing with contingency factors. The paper derives the properties of the relative Banzhaf index in QCA, demonstrates how the index can be computed easily from a rudimentary truth table, and explores its insights by revisiting selected papers in international management that apply fuzzy-set QCA. It finally suggests a three-step procedure for utilizing the relative Banzhaf index when the causal structure involves both contingency effects and configurational causation.
Keywords: Qualitative comparative analysis; Banzhaf power index; causality; explanatory power

The association between dairy intake in adolescents with inflammation and risk markers of type 2 diabetes during young adulthood – results of the DONALD study - Hohoff, E; Jankovic, N; Perrar, I; Schnermann, ME; Herder, C; Nöthlings, U; Libuda, Lars; Alexy, U (Public Health Nutrition)
ABSTRACT OBJECTIVE: The aim of this analysis was to investigate whether habitual intake of total dairy (TD) or different dairy types (liquid, solid, fermented, not-fermented, low-fat, high-fat, low-sugar and high-sugar dairy) during adolescence is associated with biomarkers of low-grade inflammation as well as risk factors of type 2 diabetes in young adulthood. DESIGN: Multivariable linear regression analyses were used to investigate prospective associations between estimated TD intake as well as intake of different types of dairy and a pro-inflammatory score, based on hsCRP, IL-6, IL-18, leptin and adiponectin, and insulin resistance assessed as HOMA2-IR in an open cohort study. SETTING: Dortmund, Germany PARTICIPANTS: Data from participants (n=375) of the DOrtmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study were included, for whom at least two 3-day weighed dietary records during adolescence (median age: 11 years) and one blood sample in young adulthood (>18 years) were available. RESULTS: There was no statistically significant association between TD intake or intake of any dairy type and the pro-inflammatory score (all p>0.05). TD intake as well as each dairy type intake and insulin resistance also showed no association (all p>0.05). CONCLUSIONS: The habitual intake of dairy or individual types of dairy during adolescence does not seem to have a major impact on low-grade systemic inflammation and insulin resistance in the long term. There was no indication regarding a restriction of dairy intake for healthy children and adolescents in terms of diabetes risk reduction.
Keywords: Public Health; Environmental and Occupational Health; Nutrition and Dietetics; Medicine (miscellaneous)

Geodesic Interpolation of Frame-Wise Speaker Embeddings for the Diarization of Meeting Scenarios - Cord-Landwehr, Tobias; Boeddeker, Christoph; Zorilă, Cătălin; Doddipatla, Rama; Haeb-Umbach, Reinhold (ICASSP 2024 - 2024 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))

Noctua 2 Supercomputer - Bauer, Carsten; Kenter, Tobias; Lass, Michael; Mazur, Lukas; Meyer, Marius; Nitsche, Holger; Riebler, Heinrich; Schade, Robert; Schwarz, Michael; Winnwa, Nils; Wiens, Alex; Wu, Xin; et al. (Journal of large-scale research facilities)
Noctua 2 is a supercomputer operated at the Paderborn Center for Parallel Computing (PC2) at Paderborn University in Germany. Noctua 2 was inaugurated in 2022 and is an Atos BullSequana XH2000 system. It consists mainly of three node types: 1) CPU Compute nodes with AMD EPYC processors in different main memory configurations, 2) GPU nodes with NVIDIA A100 GPUs, and 3) FPGA nodes with Xilinx Alveo U280 and Intel Stratix 10 FPGA cards. While CPUs and GPUs are known off-the-shelf components in HPC systems, the operation of a large number of FPGA cards from different vendors and a dedicated FPGA-to-FPGA network are unique characteristics of Noctua 2. This paper describes in detail the overall setup of Noctua 2 and gives insights into the operation of the cluster from a hardware, software and facility perspective.
Keywords: Noctua 2; Supercomputer; FPGA; PC2; Paderborn Center for Parallel Computing